PERAN KOREM I62/ WIRA BHAKTI DALAM PENANGANAN BENCANA GEMPA BUMI DI NTB - Hayu Nawang (Republic of Indonesia Defense University, 2023)
The Meteorology, Climatology, and Geophysics Agency (BMKG) said that the 7.0 SR earthquake in West Nusa Tenggara (NTB) was caused by rock dimorphism in the Indo-Australian plate. The purpose of this study was to find out how Korem 162/WB was appointed as the Task Force for handling the Lombok earthquake disaster in NTB Province in 2018. This study used a descriptive qualitative method with a purposive sampling technique at Domestic Work Lecture (KKDN) activities organized by the University Disaster Management Study Program Defense. Many problems arose during the emergency response process such as limited means of communication due to the destruction of existing infrastructure, delays in the distribution of aid due to many damaged vehicles, looting of the houses of disaster victims who were being evacuated so that the TNI, Polri, other agencies and the community had to carry out sweeping. Korem 162/Wira Bhakti took an active role during the emergency response period up to the rehabilitation and reconstruction stage. Many of the problems that occurred during the disaster response period were resolved through communication and coordination inherent between relevant agencies and stakeholders. The challenge going forward is to be able to equip its members with disaster management knowledge so they can develop a territory that is resilient to disasters